Brand ambassador, product quality, and price as predictors of skincare purchase intention on Shopee - Risma Agustina; Normansyah Normansyah (Priviet Social Sciences Journal, 2026)
This study examined whether brand ambassador endorsement, product quality, and price are associated with skincare purchase intention among Shopee users in Asahan Regency, North Sumatra, Indonesia. Drawing on source credibility and cue utilization theories, this study used a quantitative cross-sectional design with purposive sampling. Data were collected from 96 respondents who had purchased skincare products through Shopee within the previous 12 months and were analyzed using multiple linear regression. The results show that brand ambassador endorsement is positively and significantly associated with purchase intention (B = 0.190, p = .003), while price is the strongest positive predictor (B = 0.713, p < .001). Product quality was positive but not statistically significant (B = 0.074, p = .123). The three predictors were jointly significant, with an adjusted R² of .819. Because the design was cross-sectional and all variables were self-reported, the findings were interpreted as associations rather than causal effects. This study contributes to the literature by integrating source-credibility and cue-utilization perspectives in a regency-level Indonesian e-commerce skincare market and cautiously interpreting the non-significant product-quality result as consistent with possible cue-use reweighting, not as direct proof of cue substitution.